Management model based on prescription audit, ABC classification method and Kaizen to improve pharmaceutical service level - Chunga, César (2024)
In a public hospital in Peru, users must go to the hospital pharmacy service to obtain prescribed medications, but it has been identified that only 47.9% of prescriptions are filled completely, which prevents the delivery of all the medications needed to comply with the treatment indicated by the treating physician. This reveals a low level of service in the hospital pharmacy, according to the evaluation carried out during the period from January to December 2022. The causes of the problem include the inappropriate prescription of medicines, in the sense that sometimes the treating physician prescribes medicines that are not included in the Drug Formulary approved by the Ministry of Health, which means that the patient sometimes has to purchase the medicines in private pharmacies. In addition, another cause is the lack of training of warehouse personnel. In this sense, the patient care management model was developed, based on the integration of methodologies such as the audit of medical prescriptions to address the lack of availability, the implementation of the ABC method whose purpose was the better control of medicines with higher economic rotation and higher consumption; as well as the implementation of training sessions with Kaizen approach to improve the processes in the warehouse management during the period from January to March 2023. This integration resulted in a significant increase in the complete dispensing of prescriptions, from 36% to 55%. In addition, there was an improvement in staff competencies in warehouse management, with the number of trained personnel increasing from 40% to 80%. These results highlight the positive impact of the improvements implemented in the processes of planning, storage and dispensing of medicines in the hospital pharmacy.